GeoCapabilities 3-knowledge and values in education for the Anthropocene - Mitchell, David (International research in geographical and environmental education, 2022)
The GeoCapabilities project asks how powerful geographical knowledge can be brought into a curriculum to enhance students' capabilities to be free to make choices for a life they value. This paper reports on the GeoCapabilities phase 3 project which explored the social justice dimension of GeoCapabilities by working with teachers and students in challenging schools. The capabilities lens, made practical through tools for curriculum making and evaluation, shows how geographical knowledge (of migration in this case) can enhance a person's capabilities to make real choices about how to live. It also shows that the affective dimension is strongly connected to geographical knowledge including feelings, moral standpoints and values. The inequalities, injustices, fears and hopes raised when students engage with migration geography, open a space for thinking about problems, causes and alternative futures, inviting a critical lens to how political economy shapes the world. The literature and the project of GeoCapabilities have focussed on powerful disciplinary knowledge. Whilst geographical knowledge is a crucial component, I argue that an exclusive attention to disciplinary knowledge may be misleading and the concept of geographical capabilities should broaden to attend to how knowledge across disciplines, feelings, attitudes and values operate together for futures-oriented capabilities.